The Broken Chain: Evidence against Emotionally Driven Upstream Indirect Reciprocity - Wendelin Schnedler (Institute of Labor Economics (IZA), 2022)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed 'pay forward' specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: D91; C91; D03; 330; indirect upstream reciprocity; paying-it-forward; chain of unkindness; simple anger; emotional regulation; imitation